Dampak Mekanisme Good Corporate Governance pada Carbon Emission Disclosure - Eka Chandra Pramuditya, I Dewa Gede Ngurah; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi, 2020)
The research’s objective is to figure out and find empirical evidence regarding the influence of institutional ownership, foreign ownership, independent board of commissioners, and audit committee as Good Corporate Governance proxies on Carbon Emission Disclosure in mining sector companies registered on the Indonesia Stock Exchange (IDX) 2014-2019. This research analyzed the data by multiple linear regression analysis. Based on the data that has been analyzed, institutional ownership has no impact on Carbon Emission Disclosure, foreign ownership has no impact on Carbon Emission Disclosure, the independent board of commissioners has no impact on Carbon Emission Disclosure, and the audit committee has a positive impact on Carbon Emission Disclosure. Keywords: Institutional Ownership; Foreign Ownership; Independent Board Of Commissioners; Audit Committee; Carbon Emission Disclosure.